Sex-dependent toxoplasmosis-associated differences in testosterone concentration in humans - Flegr, J; Lindová, J; Kodym, P (Parasitology, 2008)
Several lines of indirect evidence suggest that subjects with latent infection of the coccidian parasite Toxoplasma gondii have a higher concentration of testosterone than uninfected controls. Here, we searched for direct evidence of latent toxoplasmosis-associated differences in testosterone concentration among a population of 174 female and 91 male students screened for Toxoplasma infection. We have found Toxoplasma-infected men to have a higher concentration of testosterone and Toxoplasma-infected women to have a lower concentration of testosterone than Toxoplasma-free controls. The opposite direction of the testosterone shift in men compared to women can explain the observed gender specificity of behavioural shifts in Toxoplasma-infected subjects.
Keywords: toxoplazmóza; Saliva; Antibodies, Protozoan; mladiství; sexuální faktory; mužské pohlaví; Testosterone; Adult; testosteron; sliny; věkové faktory; Toxoplasmosis; ženské pohlaví; ELISA; zvířata; Humans; komplement fixační testy; Sex Factors; Toxoplasma; protilátky protozoální; Complement Fixation Tests; Age Factors; Enzyme-Linked Immunosorbent Assay; dospělí; Female; Adolescent; lidé; Male; Animals